2020
DOI: 10.1021/acs.langmuir.0c02572
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Gas–Liquid Interfaces by Dissipative Particle Dynamics: Adsorption and Surface Tension of Cetyl Trimethyl Ammonium Bromide at the Air–Water Interface

Abstract: Adsorption of surfactants at gas–liquid interfaces that causes reduction in the surface tension is a classical problem in colloid and interface science with multiple practical applications in oil and gas recovery, separations, cosmetics, personal care, and biomedicine. Here, we develop an original coarse-grained model of the liquid–gas interface within the conventional dissipative particle dynamics (DPD) framework with the goal of quantitatively predicting the surface tension in the presence of surfactants. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 107 publications
(196 reference statements)
0
16
0
Order By: Relevance
“…Cationic surfactants exhibit a wide range of self-assembled geometries ranging from spherical micelles to short rods (ellipsoidal) or long cylinders to entangled worm-like micelles, vesicles, and liquid crystalline edifices, giving an account of their concentration in aqueous solution. Studies have reported that these nanoscale morphologies can be fine-tuned by altering the solution environment in the presence of various organic/inorganic additives (anionic hydrotropes, short chain surfactants, salts, etc.) manipulating the temperature, pH, ionic strength, etc. Such alteration in micellar characteristics impart them the ability to serve as smart materials with excellent potential for rheology control, enhanced oil recovery, delivery of hydrophobic bioactive molecules, etc. However, to achieve microstructures of higher order, such as worm-like micelles, vesicles, or liquid crystals, the appropriate selection of additives is very crucial.…”
Section: Introductionmentioning
confidence: 99%
“…Cationic surfactants exhibit a wide range of self-assembled geometries ranging from spherical micelles to short rods (ellipsoidal) or long cylinders to entangled worm-like micelles, vesicles, and liquid crystalline edifices, giving an account of their concentration in aqueous solution. Studies have reported that these nanoscale morphologies can be fine-tuned by altering the solution environment in the presence of various organic/inorganic additives (anionic hydrotropes, short chain surfactants, salts, etc.) manipulating the temperature, pH, ionic strength, etc. Such alteration in micellar characteristics impart them the ability to serve as smart materials with excellent potential for rheology control, enhanced oil recovery, delivery of hydrophobic bioactive molecules, etc. However, to achieve microstructures of higher order, such as worm-like micelles, vesicles, or liquid crystals, the appropriate selection of additives is very crucial.…”
Section: Introductionmentioning
confidence: 99%
“…We use the dissipative particle dynamics (DPD) approach [72][73][74][75] to model the time evolution and self-assembly in bottlebrush-solvent systems. DPD is a computationally efficient mesoscale approach that has been utilized to model a broad variety of polymer systems [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94], including studies of the effects of solvent quality on structural characteristics [95][96][97][98] and self-assembly in various polymer systems [23,79,89]. Herein, we briefly introduce the DPD approach, the details of this approach can be found in [72][73][74].…”
Section: Methodsmentioning
confidence: 99%
“…The lateral force was given by P L (Z) = 1/2[P xx (Z) + P yy (Z)] with the pressure tensor component in the Z direction. The reality units could be transformed from the mean surface tension satisfied using the simulations by γ = γ sim × k B T/R c 2 , with R c = 0.711 nm and T = 298 K [39].…”
Section: Influence Of Oil-water Ratio On the Transformation Of W/o An...mentioning
confidence: 99%
“…Th lateral force was given by PL(Z) = 1/2[Pxx(Z) + Pyy(Z)] with the pressure tensor componen in the Z direction. The reality units could be transformed from the mean surface tensio satisfied using the simulations by γ = γsim × kBT/Rc 2 , with Rc = 0.711 nm and T = 298 K [39] As the same content of oil and water as the oil/water = 1/1, surfactants adsorb at a fla interface and form a layer-like aggregate. The highest mean interfacial tension and end t end distance of H1T1 indicate that the surfactant molecular chain is most extended an has the weakest surfactant activity and emulsification capacity.…”
Section: Influence Of Oil-water Ratio On the Transformation Of W/o An...mentioning
confidence: 99%
See 1 more Smart Citation